LARVICIDAL ACTIVITY OF BACILLUS THURINGIENSIS ISOLATED FROM Bt COTTON RHIZOSPHERE SOIL AGAINST ANOPHELES MOSQUITO LARVAE (CULICIDAE) - Rajendran, Janani; Subramanian, Nathiya; Velu, Rajesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to isolate and identify Bacillus thuringiensis (Bt) from Bt cotton rhizosphere soil and analyze its larvicidal activity against Anopheles mosquito larvae. Methods: Soil samples were collected from Bt cotton field, and B. thuringiensis was isolated and characterized by biochemical and microscopical characterization. Crystal (Cry) proteins were extracted and analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and its larvicidal activity was checked by mortality analysis. Effective Bt isolates were identified by 16S rRNA sequencing. Results: A total of 24 isolates were characterized as Bacillus sp. by biochemical characterization. Further, parasporal inclusion and Cry proteins were extracted, and it was quantified by Bradford assay. The precipitated Cry proteins were analyzed by SDS-PAGE and the results have indicates Cry I protein at 100kDa, Cry3 protein at 44kDa, and cytolytic protein (Cyt) at 29kDa in most of the isolates. Larvicidal activity was checked by the 4th instar Anopheles mosquito larvae. Among the tested isolates, RBL10 and RBL20 have shown the highest percentage of larvicidal activity at 96 and 83%, respectively. Further, the two isolates RBL10 and RBL20 were identified as Bt by 16S rRNA sequencing. Conclusion: B. thuringiensis producing Cry and Cyt proteins posses potential larvicidal activity against Anopheles mosquito larvae which has biological and economic importance in mosquito control.